Impact of Regional Climate Change on the Development of Lithium Resources in Zabuye Salt Lake, Tibet - Ding, Tao; Zheng, Mianping; Nie, Zhen; Ma, Lichun; Ye, Chuanyong; Wu, Qian; Zhao, Yuanyi; Yang, Donghui; Wang, Kai (Frontiers in Earth Science, 2022)
Climate change has important implication for the ecological environment and human social activities. The Qinghai-Tibet Plateau is a sensitive area for climate change, and the lakes on the Qinghai-Tibet Plateau are known as the “guardians” of climate change. However, there are few studies on the impact of climate variations on the exploitation of lithium resources in salt lakes. In this work, the collected data from Zabuye Salt Lake Observation Station and the experimental data of brine at different temperatures were employed as the research objects to investigate the relationship between regional climate change and lithium resources in salt lakes. The results indicated that Zabuye Salt Lake had abundant solar energy resources from 1991 to 2020 with the annual average sunshine duration of 3,122.4 h, the average annual evaporation of 2,579.07 mm/yr, and the annual average precipitation of 168.65 mm/yr. The average annual evaporation is around 15.3 times the average annual precipitation, owing to the short rainy season and the low rainfall. The phase diagram displayed that two lithium carbonate precipitation peaks clearly appeared at 25 ℃, and no obvious precipitation peak appeared at 15 ℃, indicating that a high-grade lithium carbonate mixed salt was prone to be formed at a higher temperature while lithium ions was more inclined to enrich in brine at a lower temperature. Therefore, Zabuye Salt Lake with the characteristics of low temperature, large temperature difference, less precipitation, strong radiation and large evaporation could be applied as unique lithium resources in the salt gradient solar pond, which would play a positive role in the development of salt lake resources.